2022
DOI: 10.3390/min12020184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grinding Media Size on Ferronickel Slag Ball Milling Efficiency and Energy Requirements Using Kinetics and Attainable Region Approaches

Abstract: The aim of this study is to evaluate the effect that the size of grinding media exerts on ferronickel slag milling efficiency and energy savings. A series of tests were performed in a laboratory ball mill using (i) three loads of single size media, i.e., 40, 25.4, and 12.7 mm and (ii) a mixed load of balls with varying sizes. In order to simulate the industrial ball milling operation, the feed to the mill consisted of slag with natural size distribution less than 850 μm. Grinding kinetic modeling and the attai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Figure 2a clearly shows that from the energy-saving point of view, the 25.4-mm diameter balls improve energy efficiency for the coarse feed fraction −3.35 + 2.36 mm, whereas the process becomes inefficient when smaller or larger balls are used. This finding is consistent with the results of previous studies which indicate that there is an optimum grinding media size that maximizes the ball milling efficiency [37,42,43]. The optimum ball diameter depends on, among others, the feed-to-product size ratio, the mill dimensions, and the breakage parameters.…”
Section: Simulation Of the Product Size Distributionsupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 2a clearly shows that from the energy-saving point of view, the 25.4-mm diameter balls improve energy efficiency for the coarse feed fraction −3.35 + 2.36 mm, whereas the process becomes inefficient when smaller or larger balls are used. This finding is consistent with the results of previous studies which indicate that there is an optimum grinding media size that maximizes the ball milling efficiency [37,42,43]. The optimum ball diameter depends on, among others, the feed-to-product size ratio, the mill dimensions, and the breakage parameters.…”
Section: Simulation Of the Product Size Distributionsupporting
confidence: 92%
“…As a result, the fraction of the space between the balls at rest that is filled with material (interstitial filling) U was 50%. The power of the mill was calculated using the formula presented in a previous paper [37].…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not always when ball size distribution brings a positive result, since the efficiency of the mill is also affected by the feed size. This was shown in a recent experimental study by Petrakis and Komnitsas [47] done on ferronickel slag with particle size less than 0.85mm where a seasoned charge of balls had a lower grinding efficiency than mono-sized balls with a diameter of 25.4mm.…”
Section: Effect Of Grinding Media On the Mill Efficiencymentioning
confidence: 70%
“…Also, as the ball filling ratio increased, the influence of the ball size distribution also increased with a maximum power draw at 35% ball filling volume. Petrakis and Komnitsas [47] also found that there is an optimal specific energy input for a given ball size distribution to get the required product size.…”
Section: Effect Of Grinding Media On the Mill Energy Consumptionmentioning
confidence: 94%
See 1 more Smart Citation